Development of a time-resolved fluorescence microsphere Eu lateral flow test strip based on a molecularly imprinted electrospun nanofiber membrane for determination of fenvalerate in vegetables - Zhang, Le; Zheng, Yiliu; Shao, Hua; Xiao, Ming; Sun, Jianchun; Jin, Maojun; Jin, Fen; Wang, Jing; Abd El-Aty, A. M.; She, Yongxin (Frontiers in Nutrition, 2022)
Fenvalerate residues in fruits and vegetables may result in biological immune system disorders. Current sensor detection methods are harsh due to the shortcomings of antibody preparation and preservation conditions. Therefore, developing a recognition material with strong specificity, good stability, and low cost is of practical significance in designing a sensitive, simple, and rapid method. This study used precipitation polymerization to synthesize molecularly imprinted polymers (MIPs). The MIP was prepared into a fiber membrane using the electrostatic spinning method. After that, the fenvalerate hapten-mouse IgG-Eu fluorescent probe was synthesized, and the side flow chromatography strip was constructed to determine fenvalerate in vegetables using the immunocompetition method. The results showed that the adsorption capacity of MIP to fenvalerate was 3.65, and the adsorption capacity on MIPFM (an electrospinning membrane containing the fenvalerate MIPs) was five times that of free MIP. The test strip showed good linearity with R2 = 0.9761 within the range of 50 μg/L-1,000 μg/L. In conclusion, substituting fenvalerate monoclonal antibodies with a molecularly imprinted electrospinning membrane is ideal for rapid onsite detection of pyrethroids.